2021
DOI: 10.1111/jjns.12441
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Care Model‐based interventions on self‐management, quality of life and patient satisfaction in patients with ischemic stroke: A single‐blinded randomized controlled trial

Abstract: Aim: This study was designed to evaluate the effect of Chronic Care Model (CCM)-based interventions on primary outcomes (self-efficacy, quality of life/ QoL, patient satisfaction) and secondary outcomes (activities of daily living/ ADL, metabolic control variables, stroke knowledge level, healthy eating habits, physical activity, taking regular medication, measuring blood pressure regularly, living in harmony with the disease, outcomes regarding telephone interviews) in patients with ischemic stroke. Method:Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(40 citation statements)
references
References 43 publications
(62 reference statements)
1
39
0
Order By: Relevance
“…[10] Meanwhile, another recent study discloses that Chronic Care Model-based interventions improve satisfaction in stroke patients. [23] Our results were consistent with this finding that the WBCE program increased caregivers' satisfaction and enhanced ischemic patients' satisfaction, possibly because (1) communicating with trained nurses in time could solve the problems quickly that often occurred in the poststroke period. (2) caregivers could access specialists for consulting at home, rather than having to travel to the hospital, which obviously reduced time costs for caregivers and thus improved satisfaction of patients and caregivers.…”
Section: Discussionsupporting
confidence: 90%
“…[10] Meanwhile, another recent study discloses that Chronic Care Model-based interventions improve satisfaction in stroke patients. [23] Our results were consistent with this finding that the WBCE program increased caregivers' satisfaction and enhanced ischemic patients' satisfaction, possibly because (1) communicating with trained nurses in time could solve the problems quickly that often occurred in the poststroke period. (2) caregivers could access specialists for consulting at home, rather than having to travel to the hospital, which obviously reduced time costs for caregivers and thus improved satisfaction of patients and caregivers.…”
Section: Discussionsupporting
confidence: 90%
“…After removing duplicates, 7029 titles were screened, of which eight articles were included in the systematic review. [23][24][25][26][27][28][29][30] Finally, five studies were included in the quantitative analysis. 24,[27][28][29][30] Table 1 summarizes the participants' characteristics (n = 1030), and study details of the studies included such as the sample size, design, country, or the number of groups.…”
Section: Resultsmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30] Finally, five studies were included in the quantitative analysis. 24,[27][28][29][30] Table 1 summarizes the participants' characteristics (n = 1030), and study details of the studies included such as the sample size, design, country, or the number of groups. All the articles had two groups, [23][24][25][26][27][28]30 except the manuscript of Baykal et al 29 which had four groups.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have addressed the satisfaction of patients with NCDs with their treatment with the ultimate goal of improving the quality of delivered care. 30 , 47 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have addressed the satisfaction of patients with NCDs with their treatment with the ultimate goal of improving the quality of delivered care. 30,47 It is important to understand the socioeconomic factors that impact a patient's assessment of care when evaluating findings based on the PACIC. A Cochrane review 48 reported that studies of strategies to improve health outcomes in patients with co-morbidities in primary care frequently failed to adequately consider the impact of socio-economic factors.…”
mentioning
confidence: 99%